The Congolobe project, a multidisciplinary study of Congo deep-sea fan lobe complex: Overview of methods, strategies, observations and sampling. (August 2017) - Rabouille, C.; Olu, K.; Baudin, F.; Khripounoff, A.; Dennielou, B.; Arnaud-Haond, S.; Babonneau, N.; Bayle, C.; Beckler, J.; Bessette, S.; Bombled, B.; Bourgeois, S.; et al.
Abstract: The presently active region of the Congo deep-sea fan (around 330, 000 km 2 ), called the terminal lobes or lobe complex, covers an area of 2500 km 2 at 4700–5100 m water depth and 750–800 km offshore. It is a unique sedimentary area in the world ocean fed by a submarine canyon and a channel-levee system which presently deliver large amounts of organic carbon originating from the Congo River by turbidity currents. This particularity is due to the deep incision of the shelf by the Congo canyon, up to 30 km into the estuary, which funnels the Congo River sediments into the deep-sea. The connection between the river and the canyon is unique for major world rivers. In 2011, two cruises (WACS leg 2 and Congolobe) were conducted to simultaneously investigate the geology, organic and inorganic geochemistry, and micro- and macro-biology of the terminal lobes of the Congo deep-sea fan. Using this multidisciplinary approach, the morpho-sedimentary features of the lobes were characterized along with the origin and reactivity of organic matter, the recycling and burial of biogenic compounds, the diversity and function of bacterial and archaeal communities within the sediment, and the biodiversity and functioning of the faunal assemblages on the seafloor. Six different sites were selected for this study: Four distributed along the active channel from the lobe complex entrance to the outer rim of the sediment deposition zone, and two positioned cross-axis and at increasing distance from the active channel, thus providing a gradient in turbidite particle delivery and sediment age. This paper aims to provide the general context of this multidisciplinary study. It describes the general features of the site and the overall sampling strategy and provides the initial habitat observations to guide the other in-depth investigations presented in this special issue. Detailed bathymetry of each sampling site using 0.1–1 m resolution multibeam obtained with a remotely operated vehicle (ROV) shows progressive widening and smoothing of the channel-levees with increasing depth and reveals a complex morphology with channel bifurcations, erosional features and massive deposits. Dense ecosystems surveyed in the study area gather high density clusters of two large-sized species of symbiotic Vesicomyidae bivalves and microbial mats. These assemblages, which are rarely observed in sedimentary zones, resemble those based on chemosynthesis at cold-seep sites, such as the active pockmarks encountered along the Congo margin, and share with these sites the dominant vesicomyid species Christineconcha regab . Sedimentation rates estimated in the lobe complex range between 0.5 and 10 cm yr −1, which is 2–3 orders of magnitude higher than values generally encountered at abyssal depths. The bathymetry, faunal assemblages and sedimentation rates make the Congo lobe complex a highly peculiar deep-sea habitat driven by high inputs of terrigenous material delivered by the Congo channel-levee system.